Concurrent inspiratory muscle and cardiovascular training differentially improves both perceptions of effort and 5000 m running performance compared with cardiovascular training alone - Edwards, A. M.; Wells, C.; Butterly, R. (British Journal of Sports Medicine, 2008)
Objective: To examine whether inspiratory muscle training (IMT) is a useful additional technique with which to augment cardiovascular exercise training adaptations.